University Outreach in the Triple Helix Model of Collaboration for Entrepreneurial Development - Suteera Chanthes, (Journal of Educational Issues, 2024)
This paper presents an empirical study of the role of university outreach in the triple helix collaboration model adopted for the development of knowledge-based entrepreneurship in a community enterprise in Thailand. The triple helix model is a hybrid collaboration of university-industry-government networks for knowledge transfer and innovation development. This research project was a case study using a qualitative ground theory approach, semi-structured interviews, and documentary analysis for its data collection tools. This study investigates how a university outreach project performed by academic members of a regional university from the Northeast region of Thailand plays a role in promoting a local community enterprise to become knowledge-based entrepreneurship. The study chose a local organic rice farming community enterprise as its case study. The study discovered that the primary role of the university outreach is a source of creative knowledge required for innovative development. The knowledge delivery is via academic service financially supported by funding from a government agency. The empirical evidence showed that the participating academics delivered their knowledge service with sufficient entrepreneurial skills. Moreover, the academic service that promoted the enterprise’s business innovation significantly added economic value to its production. In addition to identifying success factors, this paper also discusses a challenge for further development for the university outreach sustaining its contribution to the triple helix collaboration by constructing systematic support from the university and promoting academic integrity for interdisciplinary research-based innovation development.